Base/B2pin2-Mediated Iodofluoroalkylation of Alkynes and Alkenes - Wu, Jianglong; Wang, Chenyu; Wang, Zhongjie; Li, Hongjun; Liu, Ruyan; Wang, Yan; Zhou, Pengsheng; Li, Dianjun; Yang, Jinhui (Synthesis, 2022)
A base/B2pin2-mediated iodofluoroalkylation of alkynes and a part of alkenes, using ethyl difluoroiodoacetate (ICF2CO2Et) or ICnF2n+1 (n = 3, 4, 6) as difluoroacetylating or perfluoroalkylating reagent, is disclosed. The reaction proceeds under mild conditions, and iododifluoroalkylation, hydrodifluoroalkylation and several perfluoroalkylation products were generated from alkynes or alkenes. Notably, this methodology provides a simple access to difluoroalkylated and perfluoroalkylated organic compounds starting from simple alkynes or alkenes.
Keywords: iodofluoroalkylation; alkynes; alkenes; ethyl 2,2-difluoro-2-iodoacetate; hydrodifluoroalkylation